Effects Of Post-Deposition Annealing Temperature And Time On Physical Properties Of Metal-Organic Decomposed Lanthanum Cerium Oxide Thin Film. - W., F. Lim; K., Y. Cheong; Lockman, Z. (2010)
Lanthanum cerium oxide (LaxCeyOz) precursor was prepared using metal-organic decomposition method. The effects of post-deposition annealing temperatures (400-1000 °C) and annealing time (15-120 minutes) in argon ambient on physical properties of the deposited film were investigated.